Alfabetização e letramento na educação infantil: análise das concepções das professoras das UMEIs do município de Belo Horizonte - Fernanda Cecilia Farias de Avila (2017)
This research aimed to identify the conceptions of teachers of Municipal Units of Early Childhood Education (UMEIs) in the city of Belo Horizonte on the work with reading and writing, with a focus on initial reading instruction and literacy. As specific objectives, the aims was to identify the profile of the teachers of UMEIs characterize them for their initial training, work experience; recognize the theoretical concepts that underlie the pedagogical practices with regard to working with the written language and analyze teacher´s conception about working with literacy and literacy in kindergarten. The study was based on the theoretical contributions of: Bakhtin (1979.1997), Vygotsky (1934/2010), Soares (1998), Smith (1985), Baptist (2010) and Kramer (2010), who consider the child to be cultural, with specific characteristics, immersed in a strongly determined by the written culture society, interested and able to take ownership of this knowledge of the object. The field research was constituted by application of a questionnaire to teachers who work with children under five years of age in UMEIs three of the nine regional municipality, as follows: Regional East, West and South-Central. We opted for a survey of quantitative methodological approach, the Survey type because interested us know which opinion and which the conceptions expressed by teachers about the teaching and learning of reading and writing among children attending Early Childhood Education institutions. The analyses showed that teachers feel that they are working writing language when proposing activities for the technology of writing learning. However, the teachers recognize the specific terms of literacy and literacy and declare that develop activities in which writing and reading are understood as social practices. The question of whether or not relevant literacy in kindergarten persists, and we believe that this question be given due to the understanding that learning the written language is still predominantly linked to learning writing technology to the detriment of its social use.